5.22+{X +3}=5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3^2\cdot\left(x+4\right)-5^2=5\cdot22\)
\(\Rightarrow9\cdot\left(x+4\right)-25=110\)
\(\Rightarrow9\cdot\left(x+4\right)=110+25\)
\(\Rightarrow9\cdot\left(x+4\right)=135\)
\(\Rightarrow x+4=\dfrac{135}{9}\)
\(\Rightarrow x+4=15\)
\(\Rightarrow x=15-4\)
\(\Rightarrow x=11\)
`#3107`
\(3^2\cdot\left(x+4\right)-5^2=5\cdot22\\ \Rightarrow3^2\left(x+4\right)=5\cdot22+5^2\\ \Rightarrow9\left(x+4\right)=110+25\\ \Rightarrow9\left(x+4\right)=135\\ \Rightarrow x+4=135\div9\\ \Rightarrow x+4=15\\ \Rightarrow x=15-4\\ \Rightarrow x=11\)
Vậy, `x = 11.`
\(a,\)\(25+3\left(x-8\right)=106.\)
\(\Rightarrow25+3x-24=106\)
\(\Rightarrow3x+1=106\)
\(\Rightarrow3x=105\)\(\Rightarrow x=35\)
\(b,3^2\left(x+4\right)-5^2=5.22\)
\(\Rightarrow9\left(x+4\right)-25=110\)
\(\Rightarrow9x+36-25=110\)
\(\Rightarrow9x+11=110\)
\(\Rightarrow9x=99\Leftrightarrow x=11\)
\(a,25:3\left(x-8\right)=106\)
\(\Rightarrow25+3x-24=106\)
\(\Rightarrow3x+1=106\)
\(\Rightarrow x=35\)
\(b,3^2\left(x+4\right)-5^2=5.22\)
\(\Rightarrow9x+36-25=110\)
=\(9x+11=110\)
\(\Rightarrow9x=99\)
\(\Rightarrow x=11\)
= 5.4 + ( x+3) = 25
20 + (x+3) = 25
x + 3 = 25 - 20 =5
x = 5 - 3 =2
a) 5.22 + (x + 3) = 52
5.4 + (x + 3) = 25
20 + (x + 3) = 25
x + 3 = 25 – 20
x + 3 = 5
x = 5 – 3 = 2
b) 23 + (x – 32) = 53 - 43
8 + (x – 9) = 125 – 64
8 + (x – 9) = 61
x – 9 = 61 – 8
x – 9 = 53
x = 53 + 9 = 62
a) \(5.2^2+\left(x+3\right)=5^2\)
\(x+3=5^2-5.2^2\)
\(x+3=25-20\)
\(x+3=5\)
\(x=2\)
b) \(2^3+\left(x-3^2\right)=5^3-4^3\)
\(8+\left(x-9\right)=125-64\)
\(x-9=53\)
\(x=62\)
\(3^2\left(x+4\right)-5^2=5\cdot2^2\\ 9\left(x+4\right)-25=20\\ 9\left(x+4\right)=20+25\\ 9\left(x+4\right)=45\\ x+4=45:9\\ x+4=5\\ x=5-4\\ x=1\)
a, 5 . 2 2 - 18 : 3 2
= 5.4 – 18:9
= 20 – 2 = 18
b, 17.85+15.17 – 120
= 1445+255 – 120
= 1580
c, 2 3 . 17 - 2 3 . 14
= 2 3 . ( 17 - 14 ) = 8.3 = 24
d, 20 – [30 – 5 - 1 2 ]
= 20 – (30 – 16) = 6
5.4+(X+3)=5
20+(X+3) =3
X+3 = -17
=> X = -20
5.22+{X +3}=5
22 + { x + 3 } = 5 . 5
4 + { x + 3 } = 25
x + 3 = 25 - 4
x + 3 = 21
x = 21 - 3
x = 18